The Relationships Between Propolis Collecting Capability and_x000D_ Morphometric Features of Some Honey Bee Races and Ecotypes in_x000D_ Anatolia - (:unkn) unknown (My University, 2020)
Propolis collecting capacity of the honey bee race, Apismellifera L., distributed across Anatolia and Thrace regionsof Turkey was investigated and correlated withmorphometric characteristics. Thus, the propolis collectingbehaviour of honey bee races and ecotypes naturally havebeen in Turkey, Apis mellifera caucasica, Apis melliferacarnica, Apis mellifera syriaca and Yığılca and Muğlaecotype of Apis mellifera anatoliaca were monitored. Themean yield of annual propolis was recorded as the following;Yığılca ecotype (111.6±27.5 g colony) A. m. caucasica(104±20.7 g colony), Muğla ecotype (103±34 g colony), A.m. carnica (91.16±17.6 g colony), and A. m. syriaca (74±6.4g colony) in descending order. The highest propoliscollecting activity was recorded for the Yığılca ecotype of A.m. anatoliaca and A. m. caucasica. Morphological featuresof honey bee samples were evaluated by classicmorphometric technique to correlate propolis collectingcapability and morphological features. Morphometric resultsof the present study showed that the largest wing and leglengths belonged to Yığılca ecotype of A. m. anatoliaca andA. m. caucasica. Furthermore, Pearson correlation showed asignificant relationship between some morphometriccharacteristics including the proboscis and mandibularsections, wing length (WL), wing width (WW), femur length(FL), tibia length (TL), basitarsus length (BL), basitarsuswidth (BW), and propolis collecting capability (P<0.05).Therefore, it seems that the enlargement of certainmorphological properties with genetic tendency of the honeybee races and ecotypes, primarily the legs and wings, can leadto better propolis collecting capability.